Tenant selection factor: property manager’s perspective / Nuryanti Muhamad and Ashrof Zainuddin - Muhamad, Nuryanti; Zainuddin, Ashrof (2019)
Shopping malls are becoming new places that consumers visit where the shopping itself has changed meaning and focus. Shopping malls should focus on planning the appropriate retail tenant mix that will contribute their image and attract more visitors and shoppers. Although tenant mix selection has been a concern for shopping mall managers, no best way or strategy is offered as solving this problem. So, the objectives of this research are to identify the criteria of tenant mix selection in a shopping mall and the most important criteria of tenant mix selection in a hopping mall. In research methodology, systematically solving the research problem and issue are very important because it may be understood as a science of studying how research is done scientifically. Based on the objectives and problem statements of this research, qualitative method is the best method to be used because this study requires experience, skills, expertise and opinion by some property managers or party who responsible for managing shopping malls to help researcher to find answers of the objectives of this study. The findings of this research showed that respondents ranked each of their responses within each category of factors, at the conclusion of each interview. So the finding shows target consumers' needs and wants are the most important criteria under target market factors, while tenant’s credit record as the most vital criteria in financial factors. Moreover, tenant’s variety as the most critical criteria under retailor factors and contributing to the shopping mall image is the most significant criteria under shopping mall factors.